Analysis of Sukuk Research in Indonesia Bibliometric Approach - Lina Nugraha Rani; Nisful Laila; Dian Filianti; Dwi Wulan Ramadani (Department of Islamic Economics, IPB University, 2022)
The concept of sharia-based finance is currently growing rapidly in Indonesia. One form of sharia financial instrument that has been issued by both corporations and the state is the sukuk. Sukuk is one of the most innovative forms of product in the development of the contemporary sharia financial system. It can be concluded that sukuk is an alternative source of funding, especially for the government and corporate companies. The growth of sukuk in Indonesia has increased sharply compared to other Islamic financial instruments, the growth reaching 84% ​​per year if analyzed from 2001 to 2007. Thus, sukuk has developed into one of the most important mechanisms in increasing finance in the international capital market through an Islamically acceptable structure. This study aims to determine the development of research trends in sukuk in Indonesia published by leading journals on Islamic financial economics. The data analyzed consisted of 47 papers that Scopusindexed research publications. The data is then processed and analyzed using the VOSviewer application to find out the bibliometric map of the development of sukuk research in Indonesia.